The gospels as stories : a narrative approach to Matthew, Mark, Luke, and John - Brown, Jeannine K., 1961- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2020)
"A popular writer and teacher shows how a narrative approach illuminates each of the Gospels, helping readers see the overarching stories"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, Narrative; Narrative theology